2022
DOI: 10.1039/d2tb01544g
|View full text |Cite
|
Sign up to set email alerts
|

Biobased polymer resources and essential oils: a green combination for antibacterial applications

Abstract: To fight nosocomial infections, the excessive use of antibiotics has led to the emergence of multidrug resistant microorganisms which are now considered as a relevant public health threat by the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 306 publications
0
4
0
Order By: Relevance
“…Nanoemulsion-based formulations: Nanoemulsions are nanoscale emulsions used to enhance and deliver lipophilic drugs and essential oils. These formulations improve the absorption and bioavailability of the active principles, allowing more effective treatment in conditions such as fungal infections and skin disorders [1,[54][55][56].…”
Section: Examples Of Combination Of Nanomedicine and Herbal Medicine ...mentioning
confidence: 99%
“…Nanoemulsion-based formulations: Nanoemulsions are nanoscale emulsions used to enhance and deliver lipophilic drugs and essential oils. These formulations improve the absorption and bioavailability of the active principles, allowing more effective treatment in conditions such as fungal infections and skin disorders [1,[54][55][56].…”
Section: Examples Of Combination Of Nanomedicine and Herbal Medicine ...mentioning
confidence: 99%
“…Sago starch is an abundant and low-cost carbohydrate polymer that displays distinctive features such as biodegradability and biocompatibility and has been utilized as a capping agent that imparts added stability to the nanoparticles. Additionally, the composites fabricated from sago starch show ample thermal stability and exhibit the least amount of interference with regard to flow properties, enabling its use as an important functional biocompatible polymer required for biomedical applications . However, the poor mechanical properties in addition to water absorption abilities limit the applications of sago starch-based composites for biomedical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…11−13 Additionally, the composites fabricated from sago starch show ample thermal stability and exhibit the least amount of interference with regard to flow properties, enabling its use as an important functional biocompatible polymer required for biomedical applications. 14 However, the poor mechanical properties in addition to water absorption abilities limit the applications of sago starch-based composites for biomedical purposes. Hence, to address these limitations, the recent trend is to blend with another suitable polymer that facilitates to overcome the drawback and attain the desired properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of plant essential oils (EOs) in combination with antibiotics against a range of pathogens, such as Escherichia coli ( E. coli ) , Staphylococcus aureus ( S. aureus ), and Bacillus subtilis . [ 2–7 ] The antibacterial action of these oils is believed to involve permeating the bacterial membrane and cytoplasm. [ 8–11 ] It has been observed that EOs are not likely to induce bacterial drug resistance, and can even produce a synergistic effect with antibiotics.…”
Section: Introductionmentioning
confidence: 99%